An isolated incident / Emily Maguire. - Maguire, Emily (Hertfordshire, [England] : Lightning Books, 2018)
When 25-year-old Bella Michaels is brutally murdered in the small town of Strathdee, the community is stunned and a media storm descends. Unwillingly thrust into the eye of that storm is Bella's beloved older sister, Chris, a barmaid at the local pub, and May Norman, a young reporter sent to cover the story. Chris's ex-husband, friends, and neighbours do their best to support her. But as the days tick by with no arrest, her suspicion of those around her grows. And as May attempts to file daily reports, she finds herself reassessing her own principles.
Keywords: Murder -- Investigation -- Fiction; Sisters -- Fiction; Mass media and crime -- Fiction; Australian